PENGEMBANGAN MEDIA LEARN ANIME! BERBASIS PENDEKATAN SCAFFOLDING UNTUK PEMBELAJARAN KOSAKATA BAHASA INGGRIS UNIT ANIMALS DI KELAS III SEKOLAH DASAR - Amalina, Risma; Gusrayani, Diah; Djuanda, Dadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study developed a learning media called Learn AniMe! based on the Scaffolding approach for teaching English vocabulary on the Animals theme to third-grade elementary school students. The method used was Design and Development (D&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This web-based media integrates Google Sites and Scratch, aligned with students’ concrete operational stage. Validation results from media and material experts indicated a “highly feasible” category with scores of 88.23% and 100%, respectively. Small-group and large-group trials yielded average scores of 98.57% and 88.10%, both falling into the “excellent” category. This media is considered feasible to be used as an innovative alternative for English language learning in elementary schools.